2006
DOI: 10.1002/cphc.200600057
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Protein Interactions in the Living Cell Through the Fluorescence Decays of the Cyan Fluorescent Protein

Abstract: Using fluorescence lifetime microspectroscopy and imaging techniques, we have studied the fluorescence of cyan fluorescent protein (CFP) transiently expressed in HEK-293 cells, in the presence or absence of its fluorescence resonance energy transfer (FRET) partner, yellow fluorescent protein (YFP). When the two proteins are attached through a 27-amino-acid linker, a 33 % average efficiency of intramolecular energy transfer is accurately determined inside the cell. Additionally, we observe a systematic quenchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 68 publications
4
65
1
Order By: Relevance
“…Our dimer construct resulted in a 38.5 Ϯ 1.5% FRET efficiency that falls in the range of expected values based on their molecular structure (supplemental Fig. S2A) (42) and corresponds very well to other reported FRET efficiencies for YFP-CFP dimer constructs that varied from 25 to 42% depending on the size of the linker (35,38,40,41,43). Łukasiewicz et al (39) reported an efficiency of 36% for a CFP-YFP dimer with a linker similar to the one we used.…”
Section: Discussionsupporting
confidence: 87%
“…Our dimer construct resulted in a 38.5 Ϯ 1.5% FRET efficiency that falls in the range of expected values based on their molecular structure (supplemental Fig. S2A) (42) and corresponds very well to other reported FRET efficiencies for YFP-CFP dimer constructs that varied from 25 to 42% depending on the size of the linker (35,38,40,41,43). Łukasiewicz et al (39) reported an efficiency of 36% for a CFP-YFP dimer with a linker similar to the one we used.…”
Section: Discussionsupporting
confidence: 87%
“…[26,30]. A recent report also comments on the necessity to fit 3 decay components to CFP-YFP bulk TCSPC data in cells, although the decay parameters were not reported [12]. In the absence of crystallographic evidence, we presume that the chromophore in Cerulean can adopt two conformations, similar to the CFP.…”
Section: Accepted M Manuscriptmentioning
confidence: 82%
“…due to tautomerisation, protonation or ion binding) mean that the fluorescence decay is often complex. Such dynamic complexity must be taken into consideration when extracting quantitative information from FRET measurements, and this is an emerging area of research [12][13][14][15][16].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…A 27-amino linker was used to connect the FPs CFP and YFP (15). The mCherry-YFP tandem was developed by substituting the CFP with the mCherry from the CFP-YFP construct.…”
Section: Constructionmentioning
confidence: 99%